Pengenalan Pembuatan Laporan Keuangan pada Pekerja Migran Indonesia (PMI) Berbasis Digital - Eliana; Isma, Andika; Fathiah; Intan Novia Astuti; Farah Ivana; Indra Kesuma; Sisca Mediyanti (TEKNOVOKASI : Jurnal Pengabdian Masyarakat, 2023)
Indonesian Migrant Workers (PMI) play an important role in supporting their own country's economy, but often face challenges in managing and reporting their finances. This community service activity aims to introduce digital-based financial reporting to PMIs with the aim of improving their understanding of financial management and facilitating more accurate reporting. The method used in this community service involves counseling and training to PMI on the use of digital-based applications to record their financial transactions. In addition, they were also given a better understanding of the importance of reporting their finances routinely and accurately. In this process, PMIs are taught about basic accounting concepts and how to apply them in recording their personal finances. The results of this service showed an increase in PMI's understanding and skills in managing and reporting their finances. They are able to record transactions in a more structured manner and report their finances more accurately, which can support better financial planning and wiser decision-making. This service activity makes a positive contribution to the economic welfare of PMI and encourages the use of digital technology as an effective tool to improve their financial literacy and financial independence. In addition, this service can be the basis for further program development that supports PMI in their financial aspects.